Propagation properties of spin wave in Co2FeAl Heusler alloy ultrathin films. (25th August 2021) - Singh, Suraj; Gupta, Nanhe Kumar; Hait, Soumyarup; Chaudhary, Sujeet; Tybell, Thomas; Wahlström, Erik
Abstract: We report an investigation of spin wave propagation in ion beam sputtered Co2 FeAl Heusler alloy thin film on Si(100) substrate. The spin wave transmission spectra measured at fixed frequencies by sweeping the external applied magnetic field were used to estimate technologically relevant spin wave propagation parameters. The spin wave group velocity was found at 6.1 km s −1 with an attenuation length larger than 7 μ m. The Gilbert damping parameter was estimated to be 0.019. The frequency dependency of the group velocity decreased with increasing frequency and the attenuation length increased at low frequencies while started to decrease at larger frequencies. The amplitude of non-reciprocity also decreased with increasing frequency. The propagation parameters presented were also independently verified by time-resolved propagating spin wave spectroscopy.